A case report of cardiac cysticercosis in a returning traveller: a rare cause of myocarditis. Issue 5 (20th May 2022) - Littlewood, Simon
Abstract: Background: A 38-year-old male of Indian origin presented via ambulance directly to the cardiac catheter lab with chest pain and electrocardiogram changes suggestive of an ST-elevation myocardial infarction. Serum troponin was recorded at >10 000 ng/L. Case summary: Angiogram revealed normal coronary arteries. Echocardiography showed myocardial lesions and a subsequent cardiac magnetic resonance imaging showed myocardial cysticercosis. Discussion: This is a case of myocardial cysticercosis causing myocarditis. He was treated successfully with albendazole for Taenia solium infection and non-steroidal anti-inflammatory drugs and colchicine for myocarditis.